Effect of slaughter age on the antioxidant enzyme activity, color, and oxidative stability of Korean Hanwoo (Bos taurus coreanae) cow beef. (October 2015) - Cho, Soohyun; Kang, Geunho; Seong, Pil-Nam; Park, Beomyoung; Kang, Sun Moon
Abstract: This study investigated the effect of slaughter age on the antioxidant enzyme activity, lipid and protein oxidation, and color stability in striploins ( M. longissimus lumborum ) from Korean Hanwoo ( Bos taurus coreanae ) cows of different age groups (1.9 to 3.7, 4.0 to 4.8, 5.0 to 5.7, 6.0 to 6.9, and 7.5 to 11.5 yr). Myoglobin content and the activities of catalase, superoxide dismutase, and glutathione peroxidase were significantly ( P < 0.05) increased in older cow beef. During refrigerated storage, 2-thiobarbituric acid reactive substances and protein carbonyls were significantly ( P < 0.05) increased in the meat from the older cows. The beef from older cows was darker and had lower color stability. These findings suggest that slaughter age has a negative effect on the color and lipid stability of Hanwoo cow beef. Highlights: The antioxidant enzyme activity of Hanwoo cow beef increases with slaughter age. Slaughter age decreases the lipid stability of cow beef. Protein carbonylation is promoted in older cow beef. Color stability decreases in older cow beef.